TECHNIQUES OF VISUAL COMMUNIACTION IN ARCHITECTURAL DESIGN - Kowalczyk, Maciej Wojciech; Lewandowska, Agnieszka (Journal of Education Culture and Society, 2020)
Aim. The subject of the article are methods and techniques of architectural presentation to a diverse audience. The methods of architectural presentation as a key element in the dialogue with the future user of the designed space or building allow to present to the recipient the newly designed space to be created.Methods. The authors of the article present selected techniques of architectural presentation. The described ways of presenting the project were divided into material and virtual. The article discusses the most commonly used methods of architectural presentation such as: diagrams, visualization, physical model, virtual model, video, collage, analyzing their usefulness in terms of reliable communication in order to inform future users about planned changes. The authors describe in detail the use of architectural models as a technique used to present the project to both professional and non-professional recipients. The article discusses the pros and cons of each method.Results and Conclusion. The right choice of presentation method for the addressee allows for a better understanding of the presented idea and, as a result, for more informed choices made by the society, e.g. during public consultations, or by professional decision-making bodies in matters of public space and new architectural objects. The variety of methods of imaging the project vision available today has its individual features that favor or negatively affect the reception of works, by falsifying reality or its partial message.